T-type Voltage-Sensitive Calcium Channels Mediate Mechanically-Induced Intracellular Calcium Oscillations in Osteocytes by Regulating Endoplasmic Reticulum Calcium Dynamics - Brown, Genevieve N. (Bone, 2016)
One of the earliest responses of bone cells to mechanical stimuli is a rise in intracellular calcium (Ca(2+)), and osteocytes in particular exhibit robust oscillations in Ca(2+) when subjected to loading. Previous studies implicate roles for both the endoplasmic reticulum (ER) and T-Type voltage-sensitive calcium channels (VSCC) in these responses, but their interactions or relative contributions have not been studied. By observing Ca(2+) dynamics in the cytosol (Ca(2+)(cyt)) and the ER (Ca(2+)(ER)), the focus of this study was to explore the role of the ER and T-Type channels in Ca(2+) signaling in bone cells. We demonstrate that inhibition of T-Type VSCC in osteocytes significantly reduces the number of Ca(2+)(cyt) responses and affects Ca(2+)(ER) depletion dynamics. Simultaneous observation of Ca(2+) exchange among these spaces revealed high synchrony between rises in Ca(2+)(cyt) and depressions in Ca(2+)(ER), and this synchrony was significantly reduced by challenging T-Type VSCC. We further confirmed that this effect was mediated directly through the ER and not through store-operated Ca(2+) entry (SOCE) pathways. Taken together, our data suggests that T-Type VSCC facilitate the recovery of Ca(2+)(ER) in osteocytes to sustain mechanically-induced Ca(2+) oscillations, uncovering a new mechanism underlying the behavior of osteocytes as mechanosensors.